The Effect of Online Customer Review and Online Customer Rating on Purchase Decision with Brand Image as Mediation on Shopee Marketplace in Medan City - Pasaribu, Wilson; Sembiring, Beby Karina Fawzeea; Rini, Endang Sulistya (Indonesian Journal Publisher, 2025)
Shopee is one of the online shopping places in Indonesia that allows individuals, small shops, and brands to make online transactions. The Brand Image owned by Shopee is already known to the Indonesian people compared to several other e-commerce platforms. The purpose of this study is to analyze